2019
DOI: 10.1182/blood-2019-122597
|View full text |Cite
|
Sign up to set email alerts
|

The Total Direct Cost of Healthcare in the United States in Patients with Sickle Cell Disease: A Propensity Score Matched Analysis

Abstract: Introduction: Sickle cell disease (SCD) is an inherited blood disorder with significant healthcare resource utilization in the United States (US). The clinical management throughout the course of the disease is variable. Children born with SCD in the US receive routine comprehensive care that significantly reduces their morbidity and mortality. Upon transition to adulthood, there are marked increases in disease-related complications and morbidity. The extent to which disease management costs var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Surviving individuals incurred an average of $34 477 per year in SCD-attributable medical costs; payers bore 96% of these costs, and 4% were paid by patients OOP. Our estimates are slightly higher than Salcedo and colleagues, 29 who reported excess costs of $31 045 (2020 USD) relative to non-SCD controls in a commercially insured population. However, because controls were not matched to individuals with SCD on race, their sample is likely to include a disproportionate number of Whites, who typically have higher healthcare costs than the Black population, leading to lower attributable cost estimates.…”
Section: Discussioncontrasting
confidence: 75%
“…Surviving individuals incurred an average of $34 477 per year in SCD-attributable medical costs; payers bore 96% of these costs, and 4% were paid by patients OOP. Our estimates are slightly higher than Salcedo and colleagues, 29 who reported excess costs of $31 045 (2020 USD) relative to non-SCD controls in a commercially insured population. However, because controls were not matched to individuals with SCD on race, their sample is likely to include a disproportionate number of Whites, who typically have higher healthcare costs than the Black population, leading to lower attributable cost estimates.…”
Section: Discussioncontrasting
confidence: 75%
“…Healthcare utilization among individuals with SCD is increasing, along with the associated costs. The annual healthcare cost of managing individuals with SCD ranges from $18 859 for ages 0‐9 years old to $43 586 for ages 20‐29 years old 7 . SCD accounts for approximately $2.4 billion dollars in healthcare utilization each year, primarily due to it having one of the highest rates of readmission to the hospital 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The annual healthcare cost of managing individuals with SCD ranges from $18 859 for ages 0-9 years old to $43 586 for ages 20-29 years old. 7 SCD accounts for approximately $2.4 billion dollars in healthcare utilization each year, primarily due to it having one of the highest rates of readmission to the hospital. 8 Reasons for increased healthcare utilization are complex.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare utilization among individuals with SCD is increasing along with the associated costs. One study found the annual cost of managing individual with SCD ranged from $18,859 for ages 0 -9 to $43,586 for ages 20 -29 annually (Salcedo et al, 2019). In a different study, SCD accounted for one of the highest rates for readmission among chronic illnesses and accounted for approximately $2.4 billion dollars annually (Crego et al, 2020).…”
Section: Introductionmentioning
confidence: 99%